In vitro effect of gold and silver nanoparticles on human spermatozoa. (1st November 2012) - Moretti, E.; Terzuoli, G.; Renieri, T.; Iacoponi, F.; Castellini, C.; Giordano, C.; Collodel, G.
Summary: The cytotoxicity of Au/Ag nanoparticles (NPs) on human spermatozoa was investigated in vitro . Semen from donors were incubated (37 °C, 60′–120′) with 30, 60, 125, 250 and 500 μM Au/Ag‐NPs. Sperm motility was evaluated following WHO guidelines; sperm viability was assessed with eosin Y test. Au‐NPs were characterised and localised with field emission gun‐based scanning transmission electron microscope/energy dispersive spectroscopy and transmission electron microscopy. Both tested NPs exerted a significant dose‐dependent effect on motility and viability of human spermatozoa ( P < 0.001). Ag‐NPs seem to show a slightly elevated toxicity although not significant ( P > 0.05). Au‐NPs were localised in spermatozoa, whereas Ag‐NPs were undetectable. In conclusion, Au‐NPs and Ag‐NPs do not appear to be harmful for human spermatozoa up to high concentrations (250–500 μM) that are probably difficult to reach in vivo . It is mandatory to explore the genotoxic effect of NPs in germ cells.